Of octopuses and drones: The anti-Chinese discourse in Sonora, Mexico (1899-1932) - Rabadán Figueroa, Macrina (1996)
In this article, I intend to analyze the discriminatory discourse on the Chinese in Sonora (Mexico), 1899-1932, in order to know the criteria with which they were presented as marginal beings and confront them with their social location in Sonoran life. It seems to me that it is possible to identify a contradiction between the discourse and the experience, that is, that, despite the stereotype of the marginal and undesirable Chinese that the attacks against him can throw at us, there was a considerable level of integration of him to Sonoran society. at the end of the last century and the beginning of the current one.